Associations between inflammatory markers, body composition, and physical function: the Copenhagen Sarcopenia Study. Issue 6 (27th October 2021) - Kamper, Rikke S.; Alcazar, Julian; Andersen, Lars L.; Haddock, Bryan; Jørgensen, Niklas Rye; Hovind, Peter; Suetta, Charlotte
Abstract: Background: Chronic low‐grade inflammation has been suggested as one of the key elements in the development of sarcopenia, but in contrast to disease‐related loss of muscle mass, the role of chronic low‐grade inflammation in age‐related (primary) sarcopenia is still not clear. The aim of this study was to investigate low‐grade inflammation in relation to age and the potential association between inflammatory biomarkers and body composition, muscle strength and physical performance in a healthy Danish cohort. Methods: There were 1160 generally healthy men and women (range: 22–93 years) included. Appendicular lean mass (ALM) and visceral fat normalized to height (kg/m 2 ) was assessed by dual‐energy X‐ray absorptiometry (iDXA, GE Lunar). Muscle strength and physical performance were evaluated by handgrip strength (HGS), 30 s sit‐to‐stand performance, and maximal gait speed (GS). Systemic levels of TNF‐α, IL‐6, IL‐1β, IL‐4, IL‐13, and IFN‐γ were measured using multiplex bead‐based immunoassays (Bio‐Rad). hsCRP was assessed using latex particle‐enhanced immunoturbidimetric assays (Roche Diagnostics). Results: With age, ALM/h 2, HGS, sit‐to‐stand performance and GS decreased, whereas visceral fat/h 2 increased in both men and women ( P < 0.05). Systemic levels of hsCRP, TNF‐α, IL‐4, and IFN‐γ increased with age in men and women ( P < 0.05), while IL‐1β increased in women only ( P < 0.01). Higher levels of hsCRP were associated with lower ALM/h 2 in elderly (≥65 years) men and women ( P < 0.001). Higher levels of hsCRP were associated with lower handgrip strength in elderly women ( P < 0.05) whereas higher levels of hsCRP was not associated with lower HGS in elderly men ( P = 0.056). Higher levels of hsCRP were associated with lower GS ( P < 0.05), whereas IFN‐γ was positively associated with GS in elderly women ( P < 0.05), but not elderly men. Visceral fat index was positively associated with hsCRP in elderly men and women ( P < 0.001). Compared with elderly with normal HGS, elderly men and women with low HGS displayed higher levels of TNF‐α and hsCRP ( P < 0.05). Conclusions: With age, systemic levels of hsCRP, TNF‐α, IL‐4, and IFN‐γ increased, with hsCRP and TNF‐α being especially elevated in more physically frail elderly supporting the association between low‐grade systemic inflammation and poor physical function. In contrast, only high levels of hsCRP were weakly associated with low muscle mass and positively associated with visceral fat and low physical function, suggesting that chronic low‐grade inflammation is not the main driver of age‐related loss of muscle mass as previously suggested.